Systemic Metabolic Alterations Associated with Repeated Injections of a Modified Polyriboinosinic-Polyribocytidylic Acid Complex - Powanda, Michael C. (1977)
Polyriboinosinic acid-polyribocytidylic acid complexed with poly-1-lysine and injected intramuscularly into rats (0.3 or 3.0 mg/kg) produced fever, altered leukocyte count, slightly depressed plasma zinc, increased amino acid uptake into liver, and increased plasma acute-phase globulins two- to threefold. It is suggested that these systemic metabolic alterations are indicative of a mild inflammatory response to this drug. The metabolic alterations may have to be taken into consideration when polyriboinosinic acid-polyribocytidylic acid complexed with poly-1-lysine is used in therapy.